Effect of histidine on properties of low salt surimi gel prepared from tilapia (Oreochromis niloticus) - Mohammed Akram; Javith S; Janarthanan G; K.A. Martin Xavier; B. B. Nayak; Sanath Kumar; Amjad K. Balange (Journal of Indian Fisheries Association, 2022)
Low salt surimi was prepared from tilapia (Oreochromis niloticus) using histidine and their gel properties were investigated. The main aim of the present study is to optimize the salt (0.5, 1.0 and 1.5 %) and histidine (0.75, 1.0 and 1.25%) concentration for obtaining higher gel strength by response surface methodology using central composite design. The optimum salt concentration of 1.08 %, 1.17 %, 1.08 % and histidine concentration of 0.98 %, 0.95 %, 0.98 % were established for obtaining maximum gel strength, hardness and minimum expressible moisture content of surimi gel. The predicted maximum gel strength and hardness were 451 g.cm and 64.5 N respectively. The predicted minimum expressible moisture content was 2.75%. Additionally, whiteness, TCA soluble peptide content and protein pattern of surimi gel was evaluated. The whiteness of surimi gel was decreased with the addition of histidine. TCA soluble peptide content value was in agreement with the result of gel strength. Protein pattern revealed that the polymerization of MHC in surimi gel which had maximum gel strength and hardness. Therefore, the present study revealed that the addition of histidine could yield high quality gel from tilapia surimi in low salt condition.